Bur Hole–Based Resections of Intrinsic Brain Tumors with Exoscopic Visualization - Marenco-Hillembrand, Lina; Suarez-Meade, Paola; Chaichana, Kaisorn L. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background The primary goal of brain tumor surgery is maximal safe resection while avoiding iatrogenic injury. As surgical technology increases, it is becoming more possible to resect these lesions using minimally invasive approaches. While keyhole surgeries are being advocated, the lower limit of these approaches is unclear. Bur hole–based approaches may represent a standardized minimally invasive approach. The exoscope may provide increased visualization over standard microscopic visualization, making this approach possible. This approach has yet to be described strictly for intra-axial brain tumors.Material and Methods All patients who underwent a bur hole–based surgery of an intra-axial tumor with exoscopic visualization by the senior author from January 2018 to December 2019 were prospectively identified and patient information and outcomes were collected.Results Fifteen consecutive patients underwent surgical resection of an intrinsic brain tumor using a bur hole–based approach with exoscopic visualization. The average ± standard deviation age was 57.9 ± 24.2 years. The pathology was a metastatic brain tumor in eight patients (53%), low-grade glioma in four patients (27%), and high-grade glioma in three patients (20%). The average percent resection was 100 ± 1%, where 14 (93%) underwent gross total resection. Following surgery, the median (interquartile range) Karnofsky performance scale (KPS) score was 90 (90–90), where 11 (73%) and four patients (27%) had improved and stable KPS, respectively. Zero patients had complications. The average length of stay following surgery was 1.4 ± 0.5 days, where nine patients (60%) were discharged on postoperative day 1.Conclusion This study shows that intra-axial tumors can be resected through a bur hole–based approach with exoscopic visualization with extensive resection, minimal morbidity, and early discharge rates.
Keywords: bur hole; exoscope; keyhole; minimally invasive